Maternal Attributes and Child Minimum Acceptable Diet during COVID-19 Pandemic in Indonesia - Athiya Fadlina; Judhiastuty Februhartanty; Saptawati Bardosono (Indonesian Journal of Human Nutrition, 2021)
Appropriate complementary feeding practices must be sustained during the COVID-19 pandemic for optimal growth and development of a child. However, the studies assessing factors associated with complementary feeding practices during COVID-19 are still limited. The objective of this study was to evaluate maternal attributes and minimum acceptable diet (MAD) of 6-11-month-old children during the COVID-19 pandemic in Indonesia. This study was part of the â€œCOVID-19 Mom-Infant Studyâ€ and was conducted in all regions of Indonesia using an online survey. Chi-square or Fisher's exact test was performed to examine the relationship between MAD and maternal attributes, with a significant level at p-value <0.05. From a total of 262 data collected, 74%, 77.1%, 94.3% of the children aged 6-11 months have met MAD, MDD (minimum dietary diversity), and MMF (minimum meal frequency), respectively. Motherâ€™s education level (OR= 3.625; 95%CI [1.805 â€“ 7.280]) and working status (OR= 2.197; 95%CI [1.291 â€“ 3.895] were found associated with childâ€™s MAD. One-third of children did not receive the recommended infant and young children feeding practices. Conducting nutrition interventions to mothers with lower education and not working should be a priority under these circumstances.